Optimal behavior of responsive residential demand considering hybrid phase change materials - Shafie-khah, M. (2016)
Due to communication and technology developments, residential consumers are enabled to participate inÂ Demand Response Programs (DRPs), control their consumption and decrease their cost by usingÂ Household Energy Management (HEM) systems. On the other hand, capability of energy storage systemsÂ to improve the energy efficiency causes that employing Phase Change Materials (PCM) as thermal storageÂ systems to be widely addressed in the building applications. In this paper, an operational model of HEMÂ system considering the incorporation of more than one type of PCM in plastering mortars (hybrid PCM) isÂ proposed not only to minimize the customerâ s cost in different DRPs but also to guaranty the habitantsâ Â satisfaction. Moreover, the proposed model ensures the technical and economic limits of batteries andÂ electrical appliances. Different case studies indicate that implementation of hybrid PCM in the buildingsÂ can meaningfully affect the operational pattern of HEM systems in different DRPs. The results reveal thatÂ the customerâ s electricity cost can be reduced up to 48% by utilizing the proposed model.